Metacognitive reading strategies of ESL learners with different field independent/field dependent cognitive styles / Wang Lu - Wang, Lu (2015)
Reading is an essential skill for ESL learners and many researchers in this area believe that it involves activities such as understanding ideas, identifying information, monitoring comprehension and evaluating the reading text. Metacognitive reading strategies which refers to thinking about the reading process, planning for reading, monitoring the reading task and evaluating how one has learned has been proven by researchers to be significant to ESL/EFL reading. This study aimed to identify the metacognitive reading strategies employed by a group of ESL undergraduate students when reading English texts. Apart from that, this study also examined the relationship between students‟ metacognitive reading strategies and their cognitive style of Field Dependent/Independent. A quantitative research design was conducted to collect data from 150 undergraduate first year students. CSFT (Cognitive Style Figure Test) was used to classify students into FI and FD group and SORS (Survey of Reading Strategies) was used to identify their metacognitive reading strategies. Interview with 6 students was also carried out to confirm and support the quantitative findings. The results indicated that the subjects were aware of their metacognitive strategies and use the strategies at a high-frequency level according to the established strategy usage criteria (Oxford and Burry-stock, 1995). In addition, statistically significant difference was found between FI and FD students regarding their use of Global Reading Strategies and Support Reading Strategies, hence, the use of students‟ metacognitive reading strategies was affected by their different FI/FD cognitive styles. Pedagogical implications of these findings were discussed in relation to metacognitive reading strategies instruction.